Nutrition Status of Young Children in Periphery of Lalitpur Sub-Metropolitan City in Nepal - Paudel, Sudarshan; Pradhan, Pranil Man Singh; Limbu, Netrika Prasad Maden; Shrestha, Sushan Man; Pandeya, Pooja; Regmi, Bipana (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Under nutrition in young children is a major public health concern in countries like Nepal. Despite high rate of chronic malnutrition in young children, very less focus has been given to reduce it, thus affecting the lives of these children during adolescence. Objectives: To assess the nutritional status of young children aged between 6 to 12 years in Dukuchhap village in Lalitpur district of Nepal. Materials & Methods: A cross sectional study was conducted in all the households of Dukuchhap village in Lalitpur district during Community Diagnosis Program. Out of 338 young children, 319 were assessed by anthropometric measurements and the data was compared to the standards developed by World Health Organization. Results: A total of 319 children were assessed. Mean height, weight and BMI were high in children from Chhetri ethnicity and low in Dalit children. BMI for age was less than 5th percentile in 23.2% of children. The proportions of underweight and stunted children were 10% and 8.3% respectively. The percentage of underweight (16.9%) and stunted (12.2%) girls was more than that of boys. Conclusion: Nutritional status of young children in Dukuchhap village was found to be low especially considering the high proportion of underweight girls.